ASME 2009 3rd International Conference on Energy Sustainability, Volume 2 2009
DOI: 10.1115/es2009-90289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salt Hydrates for Compact Seasonal Thermochemical Storage

Abstract: This paper describes the characterization of four salt hydrates as potential thermochemical material for compact seasonal heat storage in the built environment. First, magnesium sulfate was investigated in detail using TG-DSC apparatus. The results of this study revealed that magnesium sulfate is able to store almost 10 times more energy than water of the same volume. However, the material was unable to take up water (and release heat) under practical conditions. A new theoretical study identified three salt h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 3 publications
0
43
0
Order By: Relevance
“…Pure calcium chloride has also been investigated as TCM at small scale (40 g of CaCl 2 $2.3H 2 O) [136,143,148]. Although the authors observed gel formation that prevents further water uptake, calcium chloride showed interesting performance compared to other salts (Fig.…”
Section: The Use Of Cacl 2 For Thermochemical Energy Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Pure calcium chloride has also been investigated as TCM at small scale (40 g of CaCl 2 $2.3H 2 O) [136,143,148]. Although the authors observed gel formation that prevents further water uptake, calcium chloride showed interesting performance compared to other salts (Fig.…”
Section: The Use Of Cacl 2 For Thermochemical Energy Storagementioning
confidence: 99%
“…Indeed, an agglomeration problem, which prevents further water uptake, is often encountered when pure calcium chloride is used as thermochemical material (TCM). This problem is due to a partial melting of calcium chloride during the charging step (dehydration) or a partial formation of a solution of the material during discharging (rehydration) [143,144]. The use of additional material, which helps stabilize the physical structure of the calcium chloride as TCM further decreases the energy storage density.…”
Section: The Use Of Cacl 2 For Thermochemical Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…The used conditions for hydration and dehydration are probably not realistic for application in residential buildings, because of the high relative humidity for hydration and high temperatures for dehydration. The temperature lift has not yet been measured but can be estimated to be too low for commercial application according to measurements by van Essen et al [15]. These problems are known for magnesium sulfate and might be addressed by the use of other salts such as magnesium chloride.…”
Section: Hydration/dehydration and Calorimetric Experimentsmentioning
confidence: 98%
“…In the OSL spectrum of the Cu-doped CsCaCl 3 , an intense peak at 345 nm is observed in addition to a peak at 430 nm. The peak at 345 nm is close to the PL shoulder at around 350 nm and can be attributed to Cu 16) and the CsCaCl 3 : Cu tablets were synthesized after drying the starting materials at 423 K. However, the dehydration might not be sufficient to remove water and OH ¹ ions, leading to the residual of OH ¹ ions that can perturb Cu + ions. To detect OSL with less noise, the emission wavelength of the activator should be significantly shorter than that of the stimulation light.…”
Section: +mentioning
confidence: 99%